Deconstruction of Peter Pan’s Character in Edward Kitsis’ and Adam Horowitz’s Once Upon a Time, Season Three (2013) - Alya Safira; Eni Nur Aeni; Mimien Aminah Sudja’ie (J-Lalite: Journal of English Studies, 2020)
The purpose of this research is to find out the deconstruction of Peter Pan’s character in Kitsis’ and Horowitz’s work as described in Barrie’s Peter Pan. Kitsis’ and Horowitz’s Once Upon a Time, Season Three is the first film that deconstructs the character of Peter Pan from Barrie’s Peter Pan. The qualitative method is used in analyzing the main data that are taken from both works, Barrie’s Peter Pan and Kitsis’ and Horowitz’s Once Upon a Time, Season Three. The data analysis starts by selecting the data from re-watching and re-reading the works. Then analyzing them using the theory of deconstruction, character and characterization and cinematography. The theory is used to find the binary opposition and analyzing the characteristics of Peter Pan in both works. The cinematography is also needed to support the analysis and strengthens the argument of the analysis from the character’s deconstruction. The result of the analysis shows that the characteristic of Peter Pan in Barrie’s Peter Pan is deconstructed from hero into villain. It shows that there are four characteristics of Peter Pan as a hero that are deconstructed, namely, honest, fearless, polite and caring. Those characteristics are deconstructed into the character of Peter Pan as a villain who is manipulative, fearful, impolite and selfish. The four characteristics that are deconstructed can be seen from Peter Pan’s action towards other characters, from other characters’ explanation or the character’s emotions through every relevant scene in the film.